THE EFFECT OF DIGITAL LITERACY, ORGANIZATIONAL SUPPORT, AND DIGITAL READINESS ON THE PERFORMANCE OF HEALTH WORKERS AT COMMUNITY HEALTH CENTERS IN BATAM CITY - Dewi Fatmawati; Mira Yona; Habibuddin Nasution; Rika Yuanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Digital transformation has significantly reshaped primary healthcare services, requiring healthcare professionals to enhance their digital competencies and adaptability. This study aims to analyze the effect of digital literacy, organizational support, and digital readiness on the performance of healthcare workers at community health centers in Batam City, Indonesia. A quantitative approach was employed using a sample of 285 respondents selected from a population of 962 healthcare workers through proportional random sampling. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS. The findings indicate that digital literacy, organizational support, and digital readiness each have a positive and significant effect on healthcare worker performance, both partially and simultaneously (F = 100.770; p < 0.001). Among the three variables, digital literacy demonstrates the most dominant influence (B = 0.357; p < 0.001), followed by organizational support (B = 0.355; p < 0.001) and digital readiness (B = 0.295; p < 0.001). These results confirm that performance improvement in primary healthcare settings requires not only individual digital competence but also supportive organizational systems and readiness for change. The study contributes empirically to digital-based human resource management in primary healthcare and emphasizes that digital transformation depends fundamentally on comprehensive human and organizational readiness.